HIV, plastic surgery and Brazil: a narrative review - Murilo Sgarbi Secanho; Balduino Ferreira de Menezes; Laisa Brandão Carvalho; Ana Beatriz Pedroso Maciel De-Oliveira; Merimar Maria Chequim; Isabella Dalsico Silva; Aristides Augusto Palhares (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: Brazil presents one of the best HIV programs globally, and one of the characteristics of this approach is multidisciplinarity, where plastic surgery is involved. Objective: To conduct a non-systematic review of what has already been published on HIV by Brazilian plastic surgeons, analyzing the main themes studied. Methods: Research at PubMed, EMBASE, MEDLINE, LILACS, SciELO, Revista Brasileira de Cirurgia Plástica with the following terms: "plastic surgery HIV", "plastic surgery AIDS", "HIV plastic surgery", "AIDS plastic surgery", "HIV" and "AIDS. Results: We found 862 articles, and after selecting those written by Brazilian plastic surgeons, we reached a final number of 15, produced by 10 institutions from 5 Brazilian states. The most addressed theme was lipodystrophy in 13 publications. Discussion: From the selected articles, it is clear the concentration in the Southeast region. The most addressed theme was lipodystrophy, and the articles on it were published after ordinance GM/MS 2582. Areas such as skin cancer, genetics and surgery for gender reassignment have not been published, although there is already content related to HIV and plastic surgery in other countries. Conclusion: Despite quality publications, there are still areas in which Brazilian plastic surgery research needs to explore concerning HIV/AIDS.